Trends in the international licence trade - Alfred Wolf (Intereconomics, 1973)
The term “international licence trade” signifies the worldwide buying and selling, across national frontiers, of technical and industrial licences. In contrast to the trade in goods, which involves the exchange of material goods, the transfer of licences concerns immaterial goods, i.e. legally protected industrial property rights (patents, registered or ornamental designs, copy rights) and unprotected technical knowledge and inventions (the so-called “know-how”).
Keywords: 330; Industrialisation Policy